Evaporation from porous building materials and its cooling potential - Gonçalves, Teresa (2015)
Evaporative cooling is a traditional strategy to improve summer comfort, which has gained renewed relevance in the context of the transition to a greener economy. Here, the potential for evaporative cooling of two common porous building materials, natural stone and ceramic brick, was evaluated. The work has relevance also to the protection of built heritage becauseevaporation underlies the problems of dampness and salt crystallization, which are so harmful and frequent in this heritage. It was observed that the drying rate of the materials is, in some cases, higher than the evaporation rate of a free water surface. Surface area measurements by a three-dimensional optical technique suggested, as probable cause of this behavior, that surface irregularity gives rise to a large effective surface of evaporation in the material. Surface temperature measurements by infrared were performed afterward during evaporation experiments outside during a hot summer day in Lisbon. Their results indicate that ordinary building materials can be very efficient evaporative media and, thus, may help in achieving higher energy efficiency while maintaining a simultaneous constructive or architectural function.